The Contribution of Polish Thinkers to the Development of the Idea of European Integration - Kawalec, Marcin (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The idea of a united Europe under a common authority has its origins in the days preceding the commonly understood beginning of integration, which has often been equated with the rise of today’s European Union. The genesis of the consolidation of the European continent can not be traced back only to the Schuman Plan, but the multiple attempts at peaceful or military merging of European territories under a joint power, starting with the Greek polis and the Roman empire. In addition, the development of the idea of European integration cannot be restricted only to Western European countries. Dating back to at least the sixteenth century, history shows that Polish representatives have contributed significantly to the development of the idea. Many of their proposals, after taking into account the factor of time, seem remarkably up-to-date today. The purpose of this paper is to outline the contribution of Polish thinkers to the development of the idea of European integration.